In vitro germination tests of Sida rhombifolia L. seeds - Pedroso, D. C.; Menezes, V. O.; Lopes, S. J.; Silva, A. C. F.; Tedesco, S. B. (Agrociencia Uruguay, 2007)
The species Sida rhombifolia L. (guanxuma) used in popular medicine, is broadly found in Brazil, however often presents high disuniformity of germination in vitro, making the studies on the medicinal value and preservation limited. This research was aimed to determine an efficient method for the in vitro seed germination in this medicinal species. The experiment was carried out in the Biology Department- Federal University of Santa Maria (UFSM) Santa Maria (RS), Brazil. The used treatments for each of the substrates were: mechanical scarification of seeds made manually with fine sandpaper; immersion in water at temperature of 60o C, for five minutes; assepsy with sodium hypochlorite at 6% and control. Mechanical scarification and immersion in water at temperature of 60o C were the most efficient methods for in vitro seed germination, and the substrates did not influence the used methods differs.